2022
DOI: 10.1038/s43705-022-00100-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome-resolved metagenomics identifies the particular genetic traits of phosphate-solubilizing bacteria in agricultural soil

Abstract: Bacteria play a key role in phosphate solubilization, but related genome-centric research on agricultural microbiomes is scarce. Here, we reconstructed 472 metagenome-assembled genomes (MAGs) covering agricultural soils from six long-term field trials across China. A total of 79 MAGs contained gcd encoding quinoprotein glucose dehydrogenase (GCD), which is the key biomarker for phosphate solubilization. Our findings showed that all GCD-MAGs represent potentially novel species, with gcd copy numbers varying fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These bacteria can also enhance N fixation especially in legume crops reducing reliance on fertilizer inputs in soils. gcd encoding quinoprotein glucose dehydrogenase (GCD) has been identified as the key biomarker for inorganic phosphate solubilization in bacteria in agriculture soils (Wu et al, 2022). In addition, the phoD encoding alkaline phosphatase, bpp encoding β‐propeller phytase are good biomarkers for evaluating soil organic P transformation abilities in bacteria (Wan et al, 2020).…”
Section: Rhizo‐microbiome: a Complete Solution For Nutrient Interdepe...mentioning
confidence: 99%
“…These bacteria can also enhance N fixation especially in legume crops reducing reliance on fertilizer inputs in soils. gcd encoding quinoprotein glucose dehydrogenase (GCD) has been identified as the key biomarker for inorganic phosphate solubilization in bacteria in agriculture soils (Wu et al, 2022). In addition, the phoD encoding alkaline phosphatase, bpp encoding β‐propeller phytase are good biomarkers for evaluating soil organic P transformation abilities in bacteria (Wan et al, 2020).…”
Section: Rhizo‐microbiome: a Complete Solution For Nutrient Interdepe...mentioning
confidence: 99%
“…The accelerated microbial P solubilization could be related to the carbon input from RM. Previous work has found that cellulose, hemicelluloses, and lignin significantly increased the abundance of PSMs and their activity of phosphatase 28,29 . For example, polysaccharide breakdown and sugar metabolism are important for stimulating phosphate solubilization 30 .…”
Section: Discussionmentioning
confidence: 99%
“…have been identified to be capable of both N fixation and P solubilization [ 183 ]. The gcd gene encoding quinoprotein glucose dehydrogenase is considered the core determinant that governs microbial phosphate solubilization [ 194 , 195 ]. The organic acids and exopolysaccharides released by microbes also help increase the contents of P and K in soil [ 196 , 197 ].…”
Section: Roles Of Microorganisms In Soil Bioremediation and The Poten...mentioning
confidence: 99%